SRL In Elementary School Students’ English Language Learning: A Case Study - Cahyaning Imani; Ive Emaliana; Sumyarto Sumyarto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Elementary education is one of the levels of education in which students’ abilities, including attitudes, knowledge, and skill are developed through a series of learning activities undertaken. Self-regulated learning (SRL) in learning activities in elementary school is one of the factors that influences students’ academic progress and it is associated with metacognitive and cognitive skills. The study was conducted in grade 4 of a public elementary school in the rural area of Tuban, East Java, from March to June 2021. The adoption of SRL is one of the factors that may encourage students to participate actively in the learning activities. By organizing their knowledge, students will acquire an ethical attitude. Students will be more self-assured and independent, and they will not be reluctant to voice their thoughts or ideas during learning activities. From the findings, among metacognitive self-regulation and cognitive strategies, cognitive strategies are the one most frequently used by students.